2006
DOI: 10.1080/08990220600700925
|View full text |Cite
|
Sign up to set email alerts
|

Pain following controlled cutaneous insertion of needles with different diameters

Abstract: By decreasing the outer diameter of a needle, the frequency of insertion pain can be reduced and may encourage patients to adhere to demanding injection regimens such as recurrent insulin administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(116 citation statements)
references
References 21 publications
1
113
0
2
Order By: Relevance
“…24 Thinner needles are generally preferred by patients as they are associated with less pain, bleeding, and bruising than thicker needles. [25][26][27] To overcome these two conflicting issues, therefore, needles such as NovoFine etw have thin-wall technology that allows a thin outer diameter while maintaining the inner diameter. Such thin-wall needles are preferred by patients.…”
Section: Discussionmentioning
confidence: 98%
“…24 Thinner needles are generally preferred by patients as they are associated with less pain, bleeding, and bruising than thicker needles. [25][26][27] To overcome these two conflicting issues, therefore, needles such as NovoFine etw have thin-wall technology that allows a thin outer diameter while maintaining the inner diameter. Such thin-wall needles are preferred by patients.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 The finest most current 8-mm needles for insulin pens are 31 gauge, corresponding to an outer diameter of 0.25 mm. These 31-gauge pen needles allow safe and effective insulin administration.…”
Section: Introductionmentioning
confidence: 99%
“…31 gauge). Previous studies have shown that a larger needle diameter is associated with a greater frequency of painful injections (9). Because all needle characteristics were the same in this study, it can be inferred that the differences in pain reported were associated with needle length.…”
Section: Discussionmentioning
confidence: 78%